Association between ultra-processed food consumption and risk of breast cancer: a systematic review and dose-response meta-analysis of observational studies - Shu, Long; Zhang, Xiaoyan; Zhu, Qin; Lv, Xiaoling; Si, Caijuan (Frontiers in Nutrition, 2023)
Background Some epidemiological studies have examined the association between consumption of ultra-processed food (UPF) and the risk of breast cancer. However, the results were inconsistent. Therefore, we carried out a systematic review and dose-response meta-analysis to examine whether an association exists between high consumption of UPF and breast cancer risk. Methods PubMed/MEDLINE, ISI Web of Science, EBSCO and CNKI databases were systematically searched from inception to May 2023. The summary relative risks (RRs) and 95% confidence intervals (CIs) associated with UPF consumption and breast cancer were calculated using a random-effects model (DerSimonian-Laird method). Heterogeneity between included studies was examined using the Cochran’s Q test and I-square (I2) statistics. Publication bias was studied by visual inspection of funnel plot asymmetry and Begg’s and Egger’s tests. Results Overall, six articles involving 462,292 participants, were eligible to be included in this study. Compared to the lowest consumption, highest consumption of UPF was related to a higher risk of breast cancer (RR = 1.10; 95%CI: 1.00–1.22, p = 0.056). Besides, the linear dose–response analysis showed that each 10% increment in UPF consumption was related to a 5% higher risk of breast cancer (RR = 1.05; 95%CI: 1.00–1.10, p = 0.048). Subgroup analyses suggested that UPF consumption was positively associated with breast cancer risk in case-control studies (RR = 1.13; 95%CI: 1.01–1.26, p = 0.028). Additionally, there was also a significant positive association between UPF consumption and breast cancer risk in the subgroup with sample size<5,000(RR = 1.17; 95%CI: 1.02–1.35, p = 0.028). Conclusion Our results indicate that higher consumption of UPF is slightly related to a higher risk of breast cancer. Further studies in particular of large prospective cohort studies are warranted to confirm these results.